Pengaruh Locus Of Control Dan Stres Kerja Terhadap Perilaku Cyberloafing Pada Karyawan RSUD Kabupaten Buton Tengah - Andini Andini; Andry Stepahnie Titing; Ismanto Ismanto (Intellektika : Jurnal Ilmiah Mahasiswa, 2023)
This study aims to analyze: (1) the effect of Locus of Control on Cyberloafing Behavior in Employees of the Hospital of Central Buton Regency. (2) Effect of Job Stress on Cyberloafing Behavior in Hospital Employees of Central Buton District. This study uses an approach with quantitative methods. Collecting data in this study using observation, documentation and questionnaires. The population of this research is the employees of the Buton Tengah District Hospital. While the sample of this study amounted to 125 employees by determining the sample using the census technique. Testing this research instrument using validity and reliability tests with SPSS 20.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 4.0. Based on the research results, it is known that the Locus Of Control variable has a negative and significant effect on cyberloafing behavior in employees of the Buton Tengah District Hospital, which is indicated by a t-statistics value of 3,728 and a p-value of 0,000. Meanwhile, the variable Job Stress has a positive and significant effect on Cyberloafing Behavior in Employees of the Hospital of Central Buton Regency, which is indicated by a t-statistics value of 3,745 and a p-value of 0,000.